E-Marketing Sistem Penjualan Motor Bekas Berbasis Android Menggunakan Metode Software Development Life Cycle Model Waterfall - Wijayanto, Wahyu; Kalifia, Anna Dina (STMIK Banjarbaru, 2024)
The main problem faced by a used motorcycle dealership Arta Jaya Motor is ineffective management and marketing. This Android application was developed to facilitate the sale of used motorcycles using the Software Development Life Cycle (SDLC) method of the Waterfall model. This application includes features such as motorcycle list, description, login, Register, checkout, and purchase history. Testing with the Black Box method shows that the application functions as expected, making it easier for buyers to find and buy motorcycles and helping dealers in product management. This application has the potential to increase marketing efficiency and dealership competitiveness.Â